Mosby's drug guide for nursing students - Skidmore-Roth, Linda (St. Louis, Missouri : Elsevier Mosby, 2013)
Mosby's Drug Guide for Nursing Students, tenth edition, is the most in-depth handbook available for nursing students! Since its first publication in 1996, more than 100 U.S. and Canadian pharmacists and consultants have reviewed the book's content closely. Today, Mosby's Drug Guide for Nursing students is more up-to-date than ever-- with features that make it easy to find critical information fast!
Individual drug monographs -- Drug categories -- Appendixes -- Index.
Includes index.
Keywords: DRUGS HANDBOOKS, MANUALS, ETC